Response of kenaf (Hibiscus canabinus) to integrated nutrient management in relation to its fibre productivity, nutrient uptake and soil properties - SAHA, A R; MAITRA, D N; MAJUMDAR, B; SAHA, S; CHOWDHURY, H (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was undertaken during 2005–06 to study the effect of combined application of inorganic fertilizer, organic manure and biofertilizer on the productivity, nutrient uptake of kenaf and soil properties. Seventy-five per cent of recommended NPK applied in conjunction with organic manures (poultry manure or farm yard manure) and biofertilizer (Azotobacter) significantly increased kenaf fibre yield over 100% NPK. Highest fibre yield (3 308 kg/ha) was recorded in 75% NPK + poultry manure + Azotobacter. The highest N (75.39 kg/ha) and P (25.18 kg/ha) uptake was recorded in 75% NPK + poultry manure + Azotobacter while the highest K (260.96 kg/ha) uptake by kenaf was recorded in 75% NPK + farmyard manure + Azotobacter treatment. Post harvest soil analysis revealed that soil fertility status was enriched in respect of organic carbon, available N, P and K where inorganic fertilizer was incorporated in association with organic manures and biofertilizer. Highest soil available N (22.22% higher than control), P (1.66 times higher than control) and K (20% higher than control) were recorded in 50% NPK+ farmyard manure + Azotobacter, 50% NPK + poultry manure + Azotobacter and 75% NPK + farmyard manure + Azotobacter, respectively. Integrated use of 75% NPK + poultry manure + Azotobacter or 75% NPK+ farmyard manure + Azotobacter was found equally good for kenaf fibre production and maintenance of soil fertility under Typic Ustochrept. Total microbial and Azotobacter populations also improved with integrated nutrient management.